Characterization and source apportionment of organic compounds in PM10 using PCA and PMF at a traffic hotspot of Delhi. (May 2018) - Gupta, Sarika; Gadi, Ranu; Sharma, S.K.; Mandal, T.K.
Highlights: OC/EC and organic molecular markers in PM10 have been analyzed. Organic markers of traffic and cooking show higher concentrations over other markers. Concentrations of most of the species are higher in winter due to favorable ambient atmospheric conditions. Source apportionment studies have been performed using PCA and PMF and the results have been compared. Traffic exhaust has been observed as a major contributor for ambient air pollution in the region. Abstract: Air quality in megacity Delhi is deteriorating with alarming particulate levels. 24 h sampling of PM10 to determine the composition, seasonal variation and sources of organic molecular markers, was done from January 2015 to December 2015, at the University campus (Indira Gandhi Delhi Technical University for Women- IGDTUW), Delhi, India. The organic fraction of PM10 is composed of a mixture of numerous organic compounds, including alkanes, alkanoic acids, carbonyl compounds, anhydrosugars, and aromatic compounds that serve as specific signatory molecules or organic tracers to their sources. The homologous chains of n -alkanes and n -alkanoic acids showed a typical distribution in the ranges of C12 –C30 . The 20 homologues generally indicate the dominance of exhausts of kitchen waste and automobiles. The diagnostic parameters and receptor models have also been used to determine the sources of organic species. A seven-factor source profile solution was provided by Positive Matrix Factorization (PMF) in comparison to 5 factors by Principal Component Analysis (PCA). Seasonal variations were also observed in winter, summer, monsoon and post-monsoon; with comparatively lower concentrations in summer than in winter for most of the organic compounds.